2019
DOI: 10.1002/jbmr.3929
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Mouse Fibroblasts into Functional Osteoblasts

Abstract: Although induced pluripotent stem cells hold promise as a potential source of osteoblasts for skeletal regeneration, the induction of pluripotency followed by directed differentiation into osteoblasts is time consuming and low yield. In contrast, direct lineage reprogramming without an intervening stem/progenitor cell stage would be a more efficient approach to generate osteoblasts. We screened combinations of osteogenic transcription factors and identified four factors, Runx2, Osx, Dlx5, and ATF4, that rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 69 publications
0
21
0
Order By: Relevance
“…[ 29 ] The results presented that the expression of CD24, GD2, and TIE2 was no significantly expression in iNPLCs, compared with hNPPCs (Figure 1i). Meanwhile, GOCircle, a gene ontology analysis to reveal the functional pathway change between different cells, [ 30 ] also showed that Wnt pathway, Shh pathway, and transforming growth factor β pathway of iNPLCs were significantly increased than ones of hDFs, which were closely related with hNPCs lineage development (Figure 1j). These findings revealed that hDFs were directly converted into iNPLCs without the state of progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
“…[ 29 ] The results presented that the expression of CD24, GD2, and TIE2 was no significantly expression in iNPLCs, compared with hNPPCs (Figure 1i). Meanwhile, GOCircle, a gene ontology analysis to reveal the functional pathway change between different cells, [ 30 ] also showed that Wnt pathway, Shh pathway, and transforming growth factor β pathway of iNPLCs were significantly increased than ones of hDFs, which were closely related with hNPCs lineage development (Figure 1j). These findings revealed that hDFs were directly converted into iNPLCs without the state of progenitor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription factors play a crucial role in guiding a source cell toward a desired target phenotype, and selecting them necessitates a comprehensive understanding of the factors significantly involved in the developmental lineage of the target cell. 10 , 23 By overexpressing transcription factors, it becomes possible to reconfigure gene regulating networks, thereby modifying the identity of the cells ( Fig. 2 ).…”
Section: Dr Methodsmentioning
confidence: 99%
“…2 ). 23 Dlx5 enhances Runx2 expression and regulates osteogenic genes, while ATF4 regulates osteocalcin and osteopontin, crucial in osteoblast differentiation and bone formation. 23 …”
Section: Dr Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an alternative source of cells that can be used as osteoblasts is desired. The ability of fibroblasts to undergo differentiation into osteoblasts has been demonstrated by some researchers 22–26 . Rheumatoid arthritis synovial fibroblasts travel from cartilage destruction sites to new locations where they reinitiate the destructive processes at distant articular cartilage surfaces and affect the function of joints 27 .…”
Section: Research Of the Stem Cell Characteristics Of Fibroblasts In ...mentioning
confidence: 99%